Exploring the need to shift from debt-based to equity-based financing in Islamic banks: the case of Malaysia - Mohd. Ariffin, Noraini; Kassim, Salina; Abdul Razak, Dzuljastri (2013)

(untitled)
Due to the prohibition of interest in the Islamic banking transactions, ideally, Islamic banks should be involved more in equity-based financing which rely on the concept of risk and profit sharing as compared to debt-based financing which is similar to conventional banks. As such, financing instruments such as Mudarabah and Musharakah supposedly become the major financing instruments offered by the Islamic banks. However, as argued in the literature, the Islamic banks today concentrate more on the debt-based financing, in particular Murabahah and Ijarah contracts compared to equity based financing (Mohd. Ariffin et. al.2009; Khan and Ahmed, 2001; Al-Omar and Iqbal, 2000; and Al-Omar and Abdel Haq, 1996). Thus, the objectives of this study is firstly to analyse the use of various modes of financing by several Islamic banks in Malaysia and Bahrain, in particular the extent of equity-based financing, secondly, to assess the perceptions of the bankers with regard to issues on concept, pricing and compliance of Shari’ah for the use of equity-based financing in Islamic banks in Malaysia, thirdly, to investigate the most critical challenges for equity-based financing in Islamic banks in Malaysia, and lastly, to examine the current practice of Musharakah Mutanaqisah that has been applied by few Islamic banks in Malaysia. By undertaking this study, it is expected to shed the lights on the extent of involvement of the Islamic banks in Malaysia in equity-based financing. More importantly, findings of this study would enable us to make some recommendations on the possible ways to shift from debt-based financing to equity-based financing in the Islamic banks as well as the needed financial infrastructure to support the adoption of the equity-based financing by the Islamic banks.